PDK4 Deficiency Suppresses Hepatic Glucagon Signaling by Decreasing cAMP Levels - Park, Bo-Yoon (Diabetes, 2018)
In fasting or diabetes, gluconeogenic genes are transcriptionally activated by glucagon stimulation of the cAMP-protein kinase A (PKA)–CREB signaling pathway. Previous work showed pyruvate dehydrogenase kinase (PDK) inhibition in skeletal muscle increases pyruvate oxidation, which limits the availability of gluconeogenic substrates in the liver. However, this study found upregulation of hepatic PDK4 promoted glucagon-mediated expression of gluconeogenic genes, whereas knockdown or inhibition of hepatic PDK4 caused the opposite effect on gluconeogenic gene expression and decreased hepatic glucose production. Mechanistically, PDK4 deficiency decreased ATP levels, thus increasing phosphorylated AMPK (p-AMPK), which increased p-AMPK–sensitive phosphorylation of cyclic nucleotide phosphodiesterase 4B (p-PDE4B). This reduced cAMP levels and consequently p-CREB. Metabolic flux analysis showed that the reduction in ATP was a consequence of a diminished rate of fatty acid oxidation (FAO). However, overexpression of PDK4 increased FAO and increased ATP levels, which decreased p-AMPK and p-PDE4B and allowed greater accumulation of cAMP and p-CREB. The latter were abrogated by the FAO inhibitor etomoxir, suggesting a critical role for PDK4 in FAO stimulation and the regulation of cAMP levels. This finding strengthens the possibility of PDK4 as a target against diabetes.